Un análisis sobre las fuentes de la responsabilidad internacional de los Estados ante el cambio climático: ¿una norma consuetudinaria en formación? - de la Orden Bosch, Gustavo (IUS ET SCIENTIA, 2024)
This paper addresses some questions that climate change raises for international law. It focuses in particular on the request for an advisory opinion submitted by the United Nations General Assembly to the International Court of Justice (ICJ) on 29 March 2023. This request is analysed as a further manifestation of the international community’s concern to clarify the international responsibility of states to prevent, mitigate and remedy the damage caused by climate change. The study argues that the ICJ could clarify obligations under existing treaties. There may also be a particular opportunity for the Court to expand its jurisprudence on other sources of international law. In particular, it asks whether the ICJ could confirm the emergence of a specific customary rule on the issue.